2011
DOI: 10.1371/journal.pone.0016103
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity to Cytomegalovirus, Inflammation, All-Cause and Cardiovascular Disease-Related Mortality in the United States

Abstract: BackgroundStudies have suggested that CMV infection may influence cardiovascular disease (CVD) risk and mortality. However, there have been no large-scale examinations of these relationships among demographically diverse populations. The inflammatory marker C-reactive protein (CRP) is also linked with CVD outcomes and mortality and may play an important role in the pathway between CMV and mortality. We utilized a U.S. nationally representative study to examine whether CMV infection is associated with all-cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
315
3
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 352 publications
(333 citation statements)
references
References 70 publications
13
315
3
2
Order By: Relevance
“…The European Prospective Investigation into Cancer (EPIC) study identified an association between higher levels of CMV-IgG and ischemic heart disease (with a hazard ratio of 1.4 when compared to seronegativity). Simanek et al reported significant associations between CMV infection and both CVD and CVD-related mortality in the US population (Simanek et al 2009(Simanek et al , 2011. Similarly, Roberts et al showed that CMV was associated with CVD mortality in a predominantly Latino population living in the US and that these associations were partly mediated by IL-6 (Roberts et al 2010).…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The European Prospective Investigation into Cancer (EPIC) study identified an association between higher levels of CMV-IgG and ischemic heart disease (with a hazard ratio of 1.4 when compared to seronegativity). Simanek et al reported significant associations between CMV infection and both CVD and CVD-related mortality in the US population (Simanek et al 2009(Simanek et al , 2011. Similarly, Roberts et al showed that CMV was associated with CVD mortality in a predominantly Latino population living in the US and that these associations were partly mediated by IL-6 (Roberts et al 2010).…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 97%
“…The association between CMV infection and atherosclerotic cardiovascular disease (CVD) is well-known from the literature (Blankenberg et al 2001;Gkrania-Klotsas et al 2012;Muhlestein et al 2000;Roberts et al 2010;Simanek et al 2009Simanek et al , 2011Spyridopoulos et al 2016). Since immunological processes are key features of atherosclerosis, it has been postulated that CMV infection increases cardiovascular mortality via immunological mechanisms.…”
Section: And Atherosclerotic Cardiovascular Complicationsmentioning
confidence: 99%
“…Data on the involvement of HHVs in human atherosclerosis are far less conclusive13 and are predominantly based on epidemiological studies. These data do not allow assessment of actual viral infection in patients because antibodies (and cell‐associated DNA) may provide evidence of past infections rather than infections that are active at the time of analysis 14, 15…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, serials of investigations indicated that AGA can be found in the serum of patients with CMV‐IgG positive (Caudie et al., 2002; Sivadon et al., 2005; Yuki, Yoshino, Sato, & Miyatake, 1990). Meanwhile, Simanek AM and co‐workers provided evidence that the CMV reaction had the relationship with chronic inflammation (Simanek et al., 2011). Therefore, we investigated the relationship between AGA and CMV‐IgG in patients with GBS in our study.…”
Section: Discussionmentioning
confidence: 99%